Subject-oriented overground walking pattern generation on a rehabilitation robot based on foot and pelvic trajectories - Low, K.H. (Procedia IUTAM, 2011)
Robotic devices have been designed to enhance motor recovery by replicating clinical motion pattern training. A rehabilitation gait system has been developed to assist the subject-centric gait rehabilitation on overground walking. Environment constraints are presented such as intermittent ground contact, impact between foot and ground, and foot clearance requirement. A subject-oriented gait pattern generation is proposed with respect to the pelvic and foot trajectory of the human gait. For simplicity, ten designated points over one gait cycle are defined to express an individual walking pattern with specific stride height and length. Gait and posture on these points are studied in terms of the trajectory of ankle and metatarsal. Furthermore, the pelvic motion serves as compensation to fulfill those predescribed foot trajectory, while the joint angles for the robotic orthosis attached to the lower limb are calculated based on the solving of inverse kinematics. Results of the initial testing indicate the effectiveness and smoothness of the desired motion generated by the gait system. The labor saving of using the developed gait system is highlighted and the performance of the gait system is evaluated by the EMG analysis of selected lower limb muscles.